Learning Functions Through Vending Machines - Callahan, James Austin (East Carolina University, 2020)
Given the prevalence of function concepts in high school math classes, students need to develop a deep conceptual understanding of the topic. Technology tasks have become a frequent tool used in the high school classroom to teach functions. Technology is thought to enhance students' understanding of functions and foster a deeper understanding. The Vending Machine Task, through GeoGebra, provides students with various virtual vending machines to make selections and determine if each machine is a function or not. In this study, I have explored the effectiveness of technology centered tasks, such as the Vending Machine Task, and studied the strategies and academic language used while completing the task. My findings will show that the Vending Machine Task, and other technology tasks, expand students’ thinking of functions and help build deeper conceptual understanding.
Keywords: Functions; High School Math